1993
DOI: 10.1002/jbmr.5650080410
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and parameters of bone metabolism in patients with acromegaly

Abstract: To assess the effect of chronically elevated plasma growth hormone (GH) levels on bone metabolism and bone mineral density (BMD), 16 patients (10 females and 6 males) with a mean age of 49.1 +/- 13.2 years (range 33-68) with active acromegaly were studied and compared to a control group of 16 sex- and age-matched subjects. BMD of the lumbar spine and two different sites of the proximal femur were measured by dual-energy x-ray absorptiometry (Norland XR-26). In the acromegalic patients the mean plasma GH concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 33 publications
(3 reference statements)
0
24
0
Order By: Relevance
“…Increased bone turnover has previously been documented in patients with acromegaly (21,22,23). Moreover, growth hormone treatment in elderly osteoporotic women has been shown to increase both bone resorption and bone formation markers (24).…”
Section: Discussionmentioning
confidence: 99%
“…Increased bone turnover has previously been documented in patients with acromegaly (21,22,23). Moreover, growth hormone treatment in elderly osteoporotic women has been shown to increase both bone resorption and bone formation markers (24).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies BMD was reported to be increased or within the reference ranges, while in other papers it was decreased [17,26,[34][35][36][37]. Conflicting data on bone mineral density might be related to gonadal status, different skeletal sites being measured, various techniques employed, subject's gender, age, and activity of the disease [28,36,38].…”
Section: Acromegalymentioning
confidence: 99%
“…It is well known that in patients with acromegaly bone turnover is increased [28,29,35]. A specific marker of bone formation, osteocalcin, is elevated in subjects with active disease [28,29,35,40,43].…”
Section: Acromegalymentioning
confidence: 99%
See 2 more Smart Citations